2019
DOI: 10.4183/aeb.2019.482
|View full text |Cite
|
Sign up to set email alerts
|

Are there Reliable Predictors for the Impaired Quality of Life in Patients With Cushing’s Syndrome?

Abstract: Context.Patients with Cushing's syndrome (CS) of any etiology experience a number of physical and psychological symptoms which impact negatively on healthrelated quality of life (HRQoL).Subjects and methods. HRQoL was measured using CushingQoL questionnaire.Results. The first part of our study was a crosssectional analysis of 141 patients with CS over a 10-year period. CushingQoL score was lower in pituitary CS compared to adrenal CS. Remission and older age were associated with better outcome on item 7 (physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Most studies (30; 81%) reported on prior interventions, including transsphenoidal surgery, adrenalectomy, radiotherapy and pharmacotherapy. Thirty‐two (86%) studies reported HRQoL burden, 12–14,18–30,33–48 4 (11%) studies reported economic burden 15–17,27 and one (3%) study reported both 25 . Eight (22%) studies reported pre−/post‐surgery outcomes 18,19,37,38,42,43,47,48 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (30; 81%) reported on prior interventions, including transsphenoidal surgery, adrenalectomy, radiotherapy and pharmacotherapy. Thirty‐two (86%) studies reported HRQoL burden, 12–14,18–30,33–48 4 (11%) studies reported economic burden 15–17,27 and one (3%) study reported both 25 . Eight (22%) studies reported pre−/post‐surgery outcomes 18,19,37,38,42,43,47,48 .…”
Section: Resultsmentioning
confidence: 99%
“…CS specific HRQoL was evaluated in 18 (49%) studies using three different PRO measures—CushingQoL questionnaire, Tuebingen Cushing's Disease Quality of Life Inventory (Tuebingen CD‐25) and QoL‐Cushing's disease (QoL‐CD) 19,22–24,26,29–31,33–40,42,43,46 . CushingQoL is a 12‐item, CS‐specific HRQoL PRO that examines patients' HRQoL over the past 4 weeks 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations